2021
DOI: 10.21203/rs.3.rs-215295/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primary Effusion Lymphoma Occurring in the Setting of Transplanted Patients: A Systematic Review of a Rare, Life-Threatening Post-Transplantation Occurrence

Abstract: Background: Primary effusion lymphoma is a rare, aggressive large B-cell lymphoma strictly linked to infection by Human Herpes virus 8/Kaposi sarcoma-associated herpes virus. In its classic form, it is characterized by body cavities neoplastic effusions without detectable tumor masses. It often occurs in immunocompromised patients, such as HIV-positive individuals. Primary effusion lymphoma may affect HIV-negative elderly patients from Human Herpes virus 8 endemic regions. So far, rare cases have been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…PEL is a rare and aggressive large B-cell lymphoma characterized by body cavities’ neoplastic effusions. A recent systematic review identified 13 cases of PEL after SOT (6 kidney, 3 heart, 2 liver, 1 bowel; of whom only 1 was HIV-positive) and 1 case after allogenic HSCT [23 ▪▪ ]. In seven cases, information on ethnic origin was provided (two Haitian; two African; two Italian; one Chinese).…”
Section: Human Herpesvirus 8-associated Disordersmentioning
confidence: 99%
“…PEL is a rare and aggressive large B-cell lymphoma characterized by body cavities’ neoplastic effusions. A recent systematic review identified 13 cases of PEL after SOT (6 kidney, 3 heart, 2 liver, 1 bowel; of whom only 1 was HIV-positive) and 1 case after allogenic HSCT [23 ▪▪ ]. In seven cases, information on ethnic origin was provided (two Haitian; two African; two Italian; one Chinese).…”
Section: Human Herpesvirus 8-associated Disordersmentioning
confidence: 99%